2017
DOI: 10.1016/j.actbio.2017.10.001
|View full text |Cite
|
Sign up to set email alerts
|

Sustained antimicrobial activity and reduced toxicity of oxidative biocides through biodegradable microparticles

Abstract: Graphical abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 32 publications
0
9
0
Order By: Relevance
“…These pH-sensitive liposome carriers allow for higher affinity to sites of infection, and subsequent release of contents. Microparticles have also shown the ability to perform similar actions, such as Sofokleous et al, who looked at the release of oxidative biocides from PLGA microparticles, which showed prolonged release and activity when introduced subcutaneously in Sprague Dawley rats [110].…”
Section: Nanoparticles As Carriers Of Antimicrobial Agents-nanoparticmentioning
confidence: 99%
“…These pH-sensitive liposome carriers allow for higher affinity to sites of infection, and subsequent release of contents. Microparticles have also shown the ability to perform similar actions, such as Sofokleous et al, who looked at the release of oxidative biocides from PLGA microparticles, which showed prolonged release and activity when introduced subcutaneously in Sprague Dawley rats [110].…”
Section: Nanoparticles As Carriers Of Antimicrobial Agents-nanoparticmentioning
confidence: 99%
“…Plasma generated H2O2 reacts with the acetyl donors of TAED and PAG to produce peracetic acid (PAA) which acts in synergy with H2O2 and other plasma generated RONS, providing a potent broad-spectrum antimicrobial solution (Figure 1). PAA at the low concentration used in this study, has been shown to be non-toxic in an animal model 15 . Further, PAA does not easily give rise to AMR 15 and is used in many industrial applications including food decontamination 17 , wastewater treatment 18 , hospital waste sterilisation 19 and medical instrument disinfection 20 .…”
mentioning
confidence: 78%
“…PAA at the low concentration used in this study, has been shown to be non-toxic in an animal model 15 . Further, PAA does not easily give rise to AMR 15 and is used in many industrial applications including food decontamination 17 , wastewater treatment 18 , hospital waste sterilisation 19 and medical instrument disinfection 20 . An advantage of PAA for these applications is that it does not leave harmful residues as it quickly decomposes to acetic acid, oxygen and water.…”
mentioning
confidence: 78%
See 1 more Smart Citation
“…1]. 18 Also, Fig. 1 shows the acetyl donor groups CH 3 CO on TAED and on the by-product AA of the TAED-H 2 O 2 reaction.…”
Section: Introductionmentioning
confidence: 99%